Self-adaptive radiative cooling based on phase change materials - Ono, Masashi; Chen, Kaifeng; Li, Wei; Fan, Shanhui (Optics express, 2018)
With the ability of harvesting the coldness of universe as a thermodynamic resource, radiative cooling technology is important for a broad range of applications such as passive building cooling, refrigeration, and renewable energy harvesting. However, all existing radiative cooling technologies utilize static structures, which lack the ability of self-adaptive tuning based on demand. Here we present the concept of self-adaptive radiative cooling based on phase change materials such as vanadium dioxide. We design a photonic structure that can adaptively turn 'on' and 'off' radiative cooling, depending the ambient temperature, without any extra energy input for switching. Our results here lead to new functionalities of radiative cooling and can potentially be used in a wide range of applications for the thermal managements of buildings, vehicles and textiles.